1996
DOI: 10.1016/s1074-3804(96)80295-7
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to major blood vessels during laparoscopy

Abstract: Major blood vessel injury is a true emergency during laparoscopic procedures. Too often, the act or fear of litigation quashes the opportunity to assess the cause and learn from the experience of others. Frequently, only through a medicolegal review can such events be evaluated. After reviewing 40 such cases, the following lessons were learned. Proper technique when inserting the Veress needle, laparoscopic cannulas, and open cannulas can prevent most such accidents. If the standard precautions during insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…The primary operations were cholecystectomy in seven patients and appendectomy in one patient. Through a medicolegal review, Soderstrom [4,5] reported 40 major blood vessel injuries during laparoscopic procedures and 47 during endoscopic procedures. Moreover, distinguishing arteries from veins is necessary in all surgical cases [6].…”
mentioning
confidence: 99%
“…The primary operations were cholecystectomy in seven patients and appendectomy in one patient. Through a medicolegal review, Soderstrom [4,5] reported 40 major blood vessel injuries during laparoscopic procedures and 47 during endoscopic procedures. Moreover, distinguishing arteries from veins is necessary in all surgical cases [6].…”
mentioning
confidence: 99%
“…According to this study, considering that open technique totally eliminates the risk of MVI as was made to believe, seems inaccurate and can create catastrophic complications as well [30]. Even cases of MVI have been reported with open Hasson technique which occurred during the skin knife incision that lacerated the aorta [6,23,30,31] and that is a major concern for slender patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…laparoskopii otwartej (open laparoskopy). Po inspekcji jamy otrzewnej, w zależności od warunków anatomicznych i zakresu planowanego zabiegu instaluje się od 1 do 3 trokarów roboczych [1][2][3].…”
Section: Wstępunclassified